Art(full) gifts: Material disruptions and conceptual proddings as creative acts of mentoring for early career art teachers. Issue 3 (1st December 2018) - Hofsess, Brooke Anne; Hanawalt, Christina
Suspicious of the categories, limits and relations of power that typically define both mentoring of early career teachers and perceptions of beginning teacher identities, we set out to experiment with practices, concepts and materials that might afford new understandings and illuminate alternative practices. We explore art(full) gifts as creative acts of mentoring that attuned us to an empathetic and responsive recognition of the more-than-human ecology of teaching in public schools. In this ecology, currents of power, cultural and social norms, spaces and materials, perceptions, affects, memories, certification and training, and relationships ebb, flow, entangle and get stuck. This article, crafted in the epistolary spirit of our arts-based correspondence with early career art teachers, generates new insights and nuances regarding the interplay between mentoring and professional identities by asking: What might become of mentoring as practice and pedagogy when explored ecologically beyond a humanistic framework?